Policy-induced internal migration : an empirical investigation of the Canadian case - Kathleen M. Day; Stanley L. Winer (Center for Economic Studies and ifo Institute (CESifo), 2005)
We investigate the influence of public policy on interprovincial migration in Canada using new aggregated migration data for 1974-1996, the longest period studied so far. We consider the consequences of regional variation in a variety of policies, and also investigate the effects of certain extraordinary events in Quebec and in the Atlantic provinces. The results indicate that while the changing bias in the unemployment insurance system may have induced some people to move to the relatively high unemployment Atlantic region, the resulting flows are likely too small to have altered regional unemployment rates. In contrast, political events in Quebec in the 1970's and the closing of the cod fishery in 1992 appear to be associated with large changes in migration patterns.
Keywords: R23; J65; J41; H7; H0; R58; 330; migration; regional disparity; public policy; unemployment insurance; conditional taxation data; Binnenwanderung; Einkommensteuerpolitik; Steuerwettbewerb; Regionale Disparität; Arbeitslosenversicherung; Kanada